Prevalence, determinants and perception of use of skin lightening products among female medical undergraduates in Nigeria - O. G. Egbi; B. Kasia (Wiley, 2021)
Abstract Background Skin Lightening Products (SLP) are common in Africa especially in Nigeria. Adverse effects from these products present a public health concern. Data on the use of these products among medical students is scanty. Objectives The aim of the study was to determine the prevalence, determinants and perception of use of SLP among female undergraduate medical students in Nigeria. Methods A cross‐sectional descriptive study was conducted among female medical students selected by convenient sampling. An on‐line survey was done with google forms using a semi‐structured self‐administered questionnaire containing participants' biodata, history, pattern and perception of use of SLP. Data was analyzed using IBM SPSS Statistics 20.0. Results A total of 110 respondents completed the study with over half (62; 56.4%) of them ranging between 20 and 24 years of age. The prevalence of SLP use was 45/110(40.9%) with facial cleansers being the commonest product used [23/45(51.1%)]. Over 80% of participants knew SLP could cause adverse effects with 'skin irritation' being the most identified [71/110(64.5%)]. Although most (80%) respondents did not think that light skin was superior to dark skin, 'removal of discoloration/dark spots' (40%) and 'cosmetic reasons' (37.8%) were the commonest reasons for use. Determinants of use of SLP were light skin color (OR 3.8, 1.572-9.318), history of use among relatives (OR 3.3, 1.384-7.793) and awareness of adverse effects (OR 3.3, 1.129-9.740). Conclusion The prevalence of use of SLP was quite high among the respondents and was predicted by 'skin color', 'use among relatives' and 'awareness of adverse effects'. Education of the general public on their adverse effects is paramount to avoid harmful use.